Adaptive Management Self-assessment tool - Corps (Mercy Corps, 2016)
The Adaptive Management self-assessment tool has been designed to help teams assess the extent to which they have a supportive environment f or adaptive management within their country program. The self-assessme nt tool helps you think about five different areas that have been iden tified as important for supporting adaptive management: 1. Culture & l eadership 2. Dynamic teams 3. Appropriate analysis 4. Responsive imple mentation & operations 5. Enabling environment (for example donor fund ing and relationships)